KAJIAN PENINGKATAN PEMANFAATAN KOTORAN SAPI MENJADI BIOGAS DENGAN METODA SWOT DAN AHP DI DESA WANGUNSARI KECAMATAN LEMBANG - P. Renosori (Universitas Tribhuwana Tunggadewi, 2011)
At present there are 400 dairy cattles belonging to the people in Wangusari village. There is only 50% of the cattle manure used as organic fertilizer and that used as biogas is only 5%. An alternative strategy is thefore needed to improve utilization of the cattle manure. In this study, SWOT analysis was applied to evaluate new strategy and its implementation. Further evaluation of the alternative strategy was conducted using Analytical Hierrcy Procees (AHP). The result showed that there were three high values as follows: continuous supervision on farmer’s group, development of biogas installation to get more effective practices, and investation improvement to install biogas equipment